Anisotropic Universe in f(G,T) Gravity - M. Farasat Shamir (Advances in High Energy Physics)
This paper is devoted to investigating the recently introduced f(G,T) theory of gravity, where G is the Gauss-Bonnet term and T is the trace of the energy-momentum tensor. For this purpose, anisotropic background is chosen and a power law f(G,T) gravity model is used to find the exact solutions of field equations. In particular, a general solution is obtained which is further used to reconstruct some important solutions in cosmological contexts. The physical quantities like energy density, pressure, and equation of state parameter are calculated. A Starobinsky-like f2(T) model is proposed which is used to analyze the behavior of universe for different values of equation of state parameter. It is concluded that presence of term T in the bivariate function f(G,T) may give many cosmologically important solutions of the field equations.